Preparation method and application of novel-structure carbon nanotube and graphite lubricating additive
By achieving in-situ growth of carbon nanotubes through microwave radiation on the graphite surface, carbon nanotubes with bristle structures @ graphite lubricating additives solve the problem that graphite is difficult to adsorb on the wear surface to form a lubricating film, and achieves efficient lubricating performance improvement.
Patent Information
- Application Number
- CN202411982783.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Due to its smooth surface and stable chemical properties, graphite is difficult to adsorb on the wear surface to form a large area of lubricating film, which limits the improvement of its lubricating performance.
By mixing graphite with ferrocene and grinding, followed by microwave radiation, the graphite absorbs microwave energy to generate an arc, achieving in-situ vertical growth of carbon nanotubes on the graphite surface, forming a bristle structure of carbon nanotubes @ graphite lubricating additive.
The efficient adhesion performance of carbon nanotube @ graphite lubricant additives is achieved, and a large amount of lubricating film can be quickly formed on the worn surface, significantly improving the lubricating performance.
Smart Images

Figure CN119776045A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubricants, and in particular relates to a preparation method and application of a new-structure carbon nanotube@graphite lubricating additive. Background Art
[0002] Friction and wear are the main causes of energy loss and mechanical failure. Lubricants are one of the most effective ways to reduce friction and wear, and are of great significance to saving energy and extending the life of machinery. Lubricants are generally composed of base oil and lubricating additives. Lubricating additives can adhere to the wear surface to form a lubricating film, thereby isolating the direct contact of the friction pair, reducing friction and wear, and forming a large-area lubricating film structure can effectively reduce friction and wear.
[0003] Graphite has a very low friction coefficient and excellent mechanical strength and thermal conductivity. It can reduce friction and wear and improve heat dissipation in lubricants. Therefore, graphite is an excellent lubricant additive. However, due to its smooth surface and stable chemical properties, it is difficult to adsorb on the wear surface to form a large-area lubricating film, which hinders the further improvement of lubrication performance. Therefore, how to improve its adsorption capacity on the wear surface by regulating the morphological structure and surface properties of graphite is the key to obtaining graphite lubricating additives with excellent wear resistance and friction reduction performance. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that graphite is difficult to be adsorbed on the wear surface to form a large-area lubricating film due to its smooth surface and stable chemical properties, and further proposes a preparation method and application of a new structure carbon nanotube@graphite lubricating additive.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing a new-structure carbon nanotube@graphite lubricating additive, comprising the following steps: mixing graphite and ferrocene and grinding them to obtain a mixed powder; subjecting the mixed powder to microwave irradiation to obtain the new-structure carbon nanotube@graphite lubricating additive.
[0007] Preferably, the mass ratio of graphite to ferrocene is 2:(0.5-4).
[0008] Preferably, the graphite is flake graphite with a particle size of 2000 mesh.
[0009] Preferably, the power of the microwave radiation is 800 W, and the time of microwave radiation is 1 to 5 minutes.
[0010] The present invention provides a new structure carbon nanotube@graphite lubricating additive prepared by the preparation method described in the above technical solution. The new structure carbon nanotube@graphite lubricating additive consists of carbon nanotubes and graphite and has a bristle structure.
[0011] Preferably, the diameter of the carbon nanotube is 50-200 nm, and the diameter of the new structure carbon nanotube@graphite lubricating additive is 5-10 μm.
[0012] The present invention provides a carbon nanotube@graphite-based lubricant, which comprises the carbon nanotube@graphite lubricating additive with a new structure as described in the above technical solution.
[0013] The present invention provides a method for preparing the carbon nanotube@graphite-based lubricant described in the above technical solution, comprising the following steps:
[0014] The carbon nanotube@graphite lubricating additive with a new structure is mixed with a solvent to prepare a dispersion liquid; the dispersion liquid is stirred and subjected to ultrasound to obtain the carbon nanotube@graphite-based lubricant.
[0015] Preferably, the concentration of the new structure carbon nanotube @ graphite lubricating additive in the dispersion is 1 to 12 wt%; the solvent includes deionized water or oil. When the solvent is deionized water, the lubricant prepared is a water-based lubricant, and a dispersant needs to be added as an auxiliary agent during the preparation of the water-based lubricant. When the solvent is oil, the lubricant prepared is an oil-based lubricant.
[0016] Preferably, the stirring and ultrasonic time are both 30 to 90 minutes, the stirring rate is 500 to 1000 r / min, and the ultrasonic power is 100 to 200W.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects:
[0018] The present invention first combines ferrocene with the graphite surface by grinding, and then performs microwave radiation. The graphite absorbs microwave energy to generate an arc, and instantly reaches the temperature required for the growth of carbon nanotubes. Then, the ferrocene is decomposed into nano-iron particles and a carbon source. The nano-iron particles serve as a catalyst to achieve the in-situ vertical growth of carbon nanotubes on the graphite surface, and finally a carbon nanotube@graphite lubricating additive with a bristle structure is obtained, which has excellent adhesion performance and can quickly form a large amount of lubricating film on the wear surface.
[0019] The preparation method provided by the invention is very simple and can be prepared in a laboratory or in industrial production, thereby realizing mass production.
[0020] The new structure carbon nanotube@graphite lubricating additive provided by the present invention can improve the use stability of equipment, reduce environmental pollution, and lower costs, and can be applied to multiple fields such as micro-machine lubrication and water-based cold rolling fluid. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 This is the SEM image of the new structure carbon nanotube@graphite lubricating additive prepared in Example 1;
[0023] Figure 2 SEM images of the new structure carbon nanotube@graphite lubricating additives prepared in Example 1 (a) and Example 2 (b);
[0024] Figure 3 The friction coefficient graph of the lubricants prepared in Examples 4-7 and Comparative Examples 1-4;
[0025] Figure 4 Backscattered scanning electron microscope images (a1, b1) and carbon element energy spectrum images (a2, b2) of the worn surfaces of the lubricants prepared in Example 4 and Comparative Example 4 after the friction test. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0028] The embodiment of the present invention provides a method for preparing a new structure carbon nanotube@graphite lubricating additive, comprising the following steps: mixing graphite and ferrocene and grinding them to obtain a mixed powder; subjecting the mixed powder to microwave irradiation to obtain the new structure carbon nanotube@graphite lubricating additive.
[0029] In a preferred embodiment, the mass ratio of graphite to ferrocene is 2:(0.5-4), and more preferably 2:(0.5-2). Ferrocene in the present invention will decompose into nano iron particles and carbon source during microwave radiation. Controlling the amount of ferrocene within the above range has the advantage of improving the dispersibility and yield of carbon nanotubes. Too little ferrocene will result in less carbon nanotube yield and incomplete growth, while too much ferrocene will lead to accumulation of catalyst particles and reduce the yield of carbon nanotubes.
[0030] In a preferred embodiment, the graphite is flake graphite with a particle size of 2000 meshes. The flake graphite used in the present invention has excellent lubrication properties.
[0031] In a preferred embodiment, the power of the microwave radiation is 800W, and the time of the microwave radiation is 1 to 5 minutes. The power and time of the microwave radiation in the present invention are used to control the reaction temperature and reaction time. Experiments have shown that controlling the power and time of the microwave radiation within the above range can make the graphite surface reach the optimal temperature for in-situ vertical growth of carbon nanotubes, and at the same time, ferrocene is decomposed into nanoparticles and carbon sources. If the power is too high and the temperature exceeds the appropriate temperature, the microscopic morphology of the carbon nanotube @ graphite lubricating additive will be destroyed. If the power is too low, the temperature will not reach the reaction temperature, resulting in incomplete reaction, which is also not conducive to the formation of carbon nanotube @ graphite lubricating additives with bristle structure.
[0032] The present invention provides a new structure carbon nanotube @ graphite lubricating additive prepared by the preparation method described in the above technical scheme, wherein the new structure carbon nanotube @ graphite lubricating additive is composed of carbon nanotubes and graphite and has a bristle structure; the diameter of the carbon nanotube is 50 to 200 nm; the mass proportion of the carbon nanotube is 5 to 12%; the diameter of the new structure carbon nanotube @ graphite lubricating additive is 5 to 10 μm.
[0033] The new-structure carbon nanotube@graphite lubricating additive provided by the present invention has a bristle structure, excellent adhesion performance, and can quickly form a large amount of lubricating film on the wear surface.
[0034] The present invention provides a carbon nanotube@graphite-based lubricant, which comprises the carbon nanotube@graphite lubricating additive with a new structure as described in the above technical solution.
[0035] The present invention provides a method for preparing the carbon nanotube@graphite-based lubricant described in the above technical solution, comprising the following steps:
[0036] The carbon nanotube@graphite lubricating additive with a new structure is mixed with a solvent to prepare a dispersion liquid; the dispersion liquid is stirred and subjected to ultrasound to obtain the carbon nanotube@graphite-based lubricant.
[0037] In a preferred embodiment, the concentration of the novel structure carbon nanotube@graphite lubricating additive in the dispersion is 1-12 wt %; and the solvent includes deionized water or oil.
[0038] In a preferred embodiment, when the solvent is deionized water, a dispersant is also added when preparing the dispersion; the amount of the dispersant is 0.1wt% of the amount of the new structure carbon nanotube @ graphite lubricating additive, and the dispersant is one of N-methyl-pyrrole compound, sodium dodecyl sulfate and polyvinyl pyrrolidone.
[0039] In a preferred embodiment, the oil is P01-15 high pressure gear oil.
[0040] In a preferred embodiment, the stirring and ultrasonic time are both 30 to 90 minutes, the stirring rate is 500 to 1000 r / min, and the ultrasonic power is 100 to 200W.
[0041] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0042] Example 1
[0043] A preparation method of a new structure carbon nanotube@graphite lubricating additive:
[0044] (1) Weigh 200 mg of graphite powder and 50 mg of ferrocene powder into an agate mortar and grind until the mixture is uniform to obtain a mixed powder; wherein the graphite powder is flake graphite with a particle size of 2000 mesh;
[0045] (2) placing the mixed powder obtained in step (1) in an alumina crucible with a cover, and then placing the alumina crucible in a microwave oven for microwave irradiation at a power of 800 W for 3 minutes, collecting the product, and obtaining a new structure carbon nanotube @ graphite lubricating additive with a diameter of 7 μm, wherein the diameter of the carbon nanotube in the new structure carbon nanotube @ graphite lubricating additive is 100 nm, and the mass proportion of the carbon nanotube is 5.4%.
[0046] Figure 1 This is a SEM image of the new structure carbon nanotube @ graphite lubricating additive prepared in Example 1, and the inset is a schematic diagram of the structure of the carbon nanotube @ graphite lubricating additive. Figure 1 It can be seen that the new structure carbon nanotube@graphite lubricating additive prepared in Example 1 of the present invention is formed by the in-situ growth of carbon nanotubes on the graphite surface. Figure 1 As can be seen in the illustration, carbon nanotubes grow vertically along the graphite surface to form a brush-like structure.
[0047] Example 2
[0048] The difference from Example 1 is that in step (1), 200 mg of ferrocene powder is weighed, and the remaining steps are the same as Example 1, to obtain a new structure carbon nanotube @ graphite lubricating additive with a diameter of 7 μm, the diameter of the carbon nanotube in the new structure carbon nanotube @ graphite lubricating additive is 100 nm, and the mass proportion of the carbon nanotube is 11.8%.
[0049] Figure 2 The SEM images of the new structure carbon nanotube@graphite lubricating additive prepared in Example 1 (a) and Example 2 (b) are shown. Figure 2 It can be seen that Example 2 ( Figure 2 (b) The number of carbon nanotubes grown on the graphite surface in the newly prepared carbon nanotube@graphite lubricant additive is compared with that in Example 1 ( Figure 2 (a)) has increased significantly.
[0050] Example 3
[0051] The difference from Example 1 is that in step (1), 400 mg of ferrocene powder is weighed, and the remaining steps are the same as Example 1, to obtain a new structure carbon nanotube @ graphite lubricating additive with a diameter of 7 μm, the diameter of the carbon nanotube in the new structure carbon nanotube @ graphite lubricating additive is 100 nm, and the mass proportion of the carbon nanotube is 8.4%.
[0052] Example 4
[0053] A method for preparing a carbon nanotube@graphite-based lubricant:
[0054] (1) 100 mg of the novel carbon nanotube@graphite lubricating additive prepared in Example 1 and 10 mg of polyvinyl pyrrolidone were added into 10 ml of deionized water to prepare a carbon nanotube@graphite dispersion with a concentration of 1 wt %;
[0055] (2) The carbon nanotube@graphite dispersion obtained in step (1) was stirred at a rate of 800 r / min for 60 min, and then ultrasonically treated at 100 W for 60 min to obtain a carbon nanotube@graphite graphite-based lubricant.
[0056] Example 5
[0057] A method for preparing a carbon nanotube@graphite oil-based lubricant:
[0058] (1) 100 mg of the novel carbon nanotube@graphite lubricating additive prepared in Example 1 was added to 10 ml of P01-15 lubricating oil to prepare a carbon nanotube@graphite dispersion with a concentration of 1 wt%;
[0059] (2) The carbon nanotube@graphite dispersion obtained in step (1) was stirred at a rate of 800 r / min for 60 min, and then ultrasonically treated at 100 W for 60 min to obtain a carbon nanotube@graphite oil-based lubricant.
[0060] Example 6
[0061] The difference from Example 4 is that the new structure carbon nanotube@graphite lubricating additive prepared in Example 1 in step (1) is replaced by the new structure carbon nanotube@graphite lubricating additive prepared in Example 2, and the rest is the same as Example 4.
[0062] Example 7
[0063] The difference from Example 4 is that the new structure carbon nanotube@graphite lubricating additive prepared in Example 1 in step (1) is replaced by the new structure carbon nanotube@graphite lubricating additive prepared in Example 3, and the rest is the same as Example 4.
[0064] Comparative Example 1
[0065] A method for preparing a graphite-based lubricant:
[0066] (1) 100 mg of graphite powder and 10 mg of polyvinyl pyrrolidone were added to 10 ml of deionized water to prepare a graphite dispersion with a concentration of 1 wt %; wherein the graphite powder was flake graphite with a particle size of 2000 mesh;
[0067] (2) The graphite dispersion obtained in step (1) was stirred at a rate of 800 r / min for 60 min, and then ultrasonically treated at 100 W for 60 min to obtain a graphite-based lubricant.
[0068] Comparative Example 2
[0069] A method for preparing a carbon nanotube water-based lubricant:
[0070] (1) 100 mg of carbon nanotube powder and 10 mg of polyvinyl pyrrolidone were added to 10 ml of deionized water to prepare a carbon nanotube dispersion with a concentration of 1 wt %; wherein the particle size of the carbon nanotube powder was 100 nm;
[0071] (2) The carbon nanotube dispersion obtained in step (1) was stirred at a rate of 800 r / min for 60 min, and then ultrasonically treated at 100 W for 60 min to obtain a carbon nanotube water-based lubricant.
[0072] Comparative Example 3
[0073] A method for preparing a carbon nanotube / graphite-based lubricant:
[0074] (1) 30 mg of carbon nanotube powder, 70 mg of graphite powder and 10 mg of polyvinyl pyrrolidone were added into 10 ml of deionized water to prepare a carbon nanotube / graphite dispersion with a concentration of 1 wt %;
[0075] (2) The carbon nanotube / graphite dispersion obtained in step (1) was stirred at a rate of 800 r / min for 60 min, and then ultrasonically treated at 100 W for 60 min to obtain a carbon nanotube / graphite-based lubricant.
[0076] Comparative Example 4
[0077] A method for preparing a carbon nanotube@graphene water-based lubricant:
[0078] (1) Weigh 200 mg of graphene powder and 50 mg of ferrocene powder in an agate mortar, grind until mixed evenly, and obtain a mixed powder; wherein the particle size of the graphene powder is 2000 mesh;
[0079] (2) placing the mixed powder obtained in step (1) in an alumina crucible with a cover, then placing the alumina crucible in a microwave oven and irradiating it with microwaves at a power of 800 W for 3 min, collecting the product, and obtaining a carbon nanotube@graphene lubricating additive;
[0080] (3) taking 100 mg of the carbon nanotube@graphene lubricating additive obtained in step (2) and 10 mg of polyvinyl pyrrolidone and adding them into 10 ml of deionized water to prepare a carbon nanotube@graphene dispersion with a concentration of 1 wt%;
[0081] (4) The carbon nanotube@graphene dispersion obtained in step (3) was stirred at a rate of 800 r / min for 60 min, and then ultrasonically treated at 100 W for 60 min to obtain a carbon nanotube@graphene water-based lubricant.
[0082] Friction performance test:
[0083] The friction performance of the lubricants prepared in Examples 4-7 and Comparative Examples 1-4 was tested using a ball-on-disc friction tester. The normal load of the test was 5 N, the linear speed was 0.05 m / s, the friction duration was 15 min, and each test was repeated 3 times to take the average value.
[0084] The friction coefficients of the lubricants prepared in Examples 4-7 and Comparative Examples 1-4 are shown in Figure 3 .Depend on Figure 3It can be seen that the friction coefficient of the new structure carbon nanotube @ graphite-based lubricant in Example 4 is as low as 0.10. Compared with the graphite-based lubricant in Comparative Example 1, the friction coefficient is reduced by 44.1%. It is confirmed that the new structure carbon nanotube @ graphite prepared by the present invention can significantly improve the lubrication performance of the lubricant as a lubricant additive. The friction coefficient of the carbon nanotube @ graphene water-based lubricant in Comparative Example 4 is 0.31, which is 210.0% higher than the new structure carbon nanotube @ graphite-based lubricant in Example 4. It shows that after graphite is replaced with graphene, its friction performance is significantly reduced. The friction coefficient of the new structure carbon nanotube @ graphite oil-based lubricant in Example 5 is 0.15, and the friction coefficient of P01-15 high-pressure gear oil is 0.41. The lubrication performance of the new structure carbon nanotube @ graphite oil-based lubricant in Example 5 is significantly better than that of P01-15 high-pressure gear oil, and the friction coefficient is reduced by 63.4%.
[0085] Figure 4 The backscattered scanning electron microscope images (a1, b1) and carbon element energy spectrum images (a2, b2) of the wear surface of the lubricant prepared in Example 4 and Comparative Example 4 after the friction test. Figure 4 It can be seen that the lubricant film coverage area of the wear surface after the friction test of the lubricant prepared in Example 4 is 56.8%, and the lubricant film coverage area of the wear surface after the friction test of the lubricant prepared in Comparative Example 4 is 25.6%.
[0086] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a new structure carbon nanotube@graphite lubricating additive, characterized in that: The method comprises the following steps: mixing graphite and ferrocene and grinding them to obtain mixed powder; subjecting the mixed powder to microwave radiation to obtain the new structure carbon nanotube@graphite lubricating additive.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the graphite to ferrocene is 2:(0.5-4).
3. The preparation method according to claim 1, characterized in that: The graphite is flake graphite with a particle size of 2000 meshes.
4. The preparation method according to claim 1, characterized in that: The power of the microwave radiation is 800W, and the time of the microwave radiation is 1 to 5 minutes.
5. The novel structure carbon nanotube@graphite lubricating additive prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The novel carbon nanotube@graphite lubricating additive consists of carbon nanotubes and graphite and has a bristle structure.
6. The novel structure carbon nanotube@graphite lubricating additive according to claim 5, characterized in that: The diameter of the carbon nanotube is 50-200 nm, and the diameter of the new structure carbon nanotube@graphite lubricating additive is 5-10 μm.
7. A carbon nanotube@graphite-based lubricant, characterized in that: The carbon nanotube@graphite-based lubricant comprises the novel structure carbon nanotube@graphite lubricating additive according to claim 5.
8. The method for preparing the carbon nanotube@graphite-based lubricant according to claim 7, characterized in that: The following steps are involved: The novel carbon nanotube@graphite lubricating additive of claim 5 is mixed with a solvent to prepare a dispersion; the dispersion is stirred and ultrasonicated to obtain the carbon nanotube@graphite-based lubricant.
9. The preparation method according to claim 8, characterized in that: The concentration of the new-structure carbon nanotube@graphite lubricating additive in the dispersion is 1-12 wt %; and the solvent includes deionized water or oil.
10. The preparation method according to claim 8, characterized in that: The stirring and ultrasonic time are both 30 to 90 minutes, the stirring rate is 500 to 1000 r / min, and the ultrasonic power is 100 to 200W.